Multicriteria evaluation of intermodal (rail/road) freight transport corridors - Janić, Milan (Logistics and sustainable transport, 2020)
This paper deals with the multi-criteria evaluation of the intermodal (rail/road) freight corridors as competing transport alternatives. For such a purpose, the methodology has been developed consisting of two main components; i) the analytical models for estimating the indicators and measures of the corridors’ physical/spatial or infrastructural, technical/technological, operational, economic, social, and environmental performance; and ii) the MCDM (Multi-Criteria Decision Making) method using the above-mentioned indicators and measures of performance as the evaluation attributes/criteria in ranking and identifying the preferred among the several mutually competing freight transport alternative corridors. The proposed methodology has been applied to two Trans-European intermodal rail/road freight transport corridors. As such, it has shown to be of use, in addition to the researchers, also to the other potential DMs (Decision Maker(s)). These could be, for example, the freight shippers/receivers as the users of the already existing intermodal (rail/road) transport services, the transport and intermodal terminal operators and infrastructure providers, and the business and policy makers facing with the problems of allocating the usually limited investments in the social-economic feasible way to the corresponding infrastructure at the local, regional, national, and international scale.
Keywords: evalvacija; indicators and measures of performance; indikatorji in merila uspešnosti; intermodal (rail/road) freight transport corridors; intermodalni (železniško/cestni) tovorni prometni koridorji; multicriteria evaluation